Run east : flight from the Holocaust - Pomerantz, Jack 1918- (Univ. of Illinois Press, 1997)
Jack Pomerantz fled east from his home in Radzyn, Poland, when the German planes attacked, walking by night and hiding in the forests of eastern Europe by day. He was just twenty-one when this saga of devastating loss and inspiring courage began. His flight took him on a harrowing, dangerous odyssey through Siberia, to Taskent, to Siberia again, and then - in Polish uniform - back to his home as a liberator. A peddler's son who had known only poverty throughout his childhood and adolescence, Pomerantz provides a poignant picture of the many Jewish refugees who had to escape not only Nazi terror but also the forces of Stalin and the NKVD, the forerunner of the KGB. Run East provides remarkable detail about a part of the Holocaust that has remained relatively unexplained - the world of European Jews who escaped into what was then the Soviet Union, only to be used by the Soviets, sometimes as laborers in Siberia and sometimes as soldiers fighting on the eastern front